The Use of Visual English Learning Media to Increase Learning Interest Among Elementary School Children in Handio Village - Nasution, Enni Efrida; Hasibuan, Maria Ulfah; Lubis, Lesna Marito; Daulay, Ence; Daulay, Intan Pertama; Nasution, Rahmi Yulianti; Hasibuan, Wanda Novria; Siregar, Siti Fadilah; Sudrajat, Rizky (PT. LITERASI SAINS NUSANTARA, 2025)
The purpose of this community service activity is to utilize competitive visual media, such as displaying images with English vocabulary, to enhance the English vocabulary acquisition of elementary school students. English is one of the subjects taught at the elementary school level and is considered an additional subject. English language proficiency is essential in the modern era and should be introduced from an early age to improve children's vocabulary absorption and comprehension. Vocabulary is one of the most critical components in learning a language. Visual media serve as an engaging and enjoyable tool for elementary students, as it allows them to learn while also playing. The use of instructional media is a supporting aspect that helps students master specific fields of study, particularly English. The results of the community service activity conducted at SDN 1403 Tiga Serangkai, Handio Village, show that songs are highly effective and can be used to introduce English vocabulary to children.